Effects of Community Size and Contact Rate in Synchronous Social Q&A - White, Ryen W.; Richardson, Matthew; Richardson, Matthew; Liu, Yandong (Proceedings of the ACM SIGCHI Conference on Human Factors in Computing Systems (CHI 2011), 2011)
Social question-and-answer (Q&A) involves the location of answers to questions through communication with people. Social Q&A systems, such as mailing lists and Web forums are popular, but their asynchronous nature can lead to high answer latency. Synchronous Q&A systems facilitate real-time dialog, usually via instant messaging, but face challenges with interruption costs and the availability of knowl-edgeable answerers at question time. We ran a longitudinal study of a synchronous social Q&A system to investigate the effects of the rate with which potential answerers were contacted (trading off time-to-answer against interruption cost) and community size (varying total number of mem-bers). We found important differences in subjective and objective measures of system performance with these varia-tions. Our findings help us understand the costs and benefits of varying contact rate and community size in synchronous social Q&A, and inform system design for social Q&A.
Best Paper